Determinantes da evasão fiscal: um estudo comparativo entre países da América Latina - Borghetti, Jonas (Universidade do Vale do Rio dos Sinos, 2013)
The high levels of tax evasion that exist in developing countries result in serious losses such as the absence of fair taxation, growth of the informal economy and loss of legitimacy of the government. Thus, this dissertation sought to determine and analyze the factors that affect the level of tax evasion in Latin America. For this, data from research carried out under the InterAmerican Centre of Tax Administrations (CIAT) covering the period 2000-2010 were used, as well as social, economic and institutional indicators of the countries measured by organizations. The analysis was conducted through a multiple regression model using panel data. The results indicated that the higher the medium age of the population, the quality of education provided, the public investment in research and development and income from urban employment, lower is the levels of tax evasion. On the other hand, the increases in crime and income inequality generate growth in evasive behavior. About the higher complexity of the legislation, the effect varies with the preponderance on the relationship between the cost to the taxpayer, when the level of tax evasion grow, and the usefulness of the information obtained as to effectively control the taxman, what reduces evasion.
Keywords: Latin America; Determinants; Tax Evasion; América Latina; Determinantes; Evasão fiscal; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis